La justicia al banquillo. La Causa de Los Jueces y las (im)posibilidades de juzgar responsables civiles de la última dictadura en Santiago del Estero (Argentina) - Florencia I. De Marco; Luis Garay (Les Cahiers ALHIM)
This paper will present preliminary reflections of an ethnographic investigation of the judicial process called “The Cause of the Judges” (9002/03 and 300029/12), included in “Megacausa III”, by the Oral Federal Criminal Court of Santiago del Estero, Argentina. This process, which took fourteen years to complete, reached trial in 2016/17 with the indictment, for the first time in the province, of two judicial officials for crimes against humanity committed during the last dictatorship in the country (1976/1983). For this purpose we explore the concept of "technical impunity" from Wlasic (2010), that means, the implementation of measures and actions aimed at delaying, limiting or preventing the prosecution of those responsible for genocidal practices. We take as a corpus of analysis the documents of the process of this case: initial complaints, investigations, resolutions, appeals filed at various levels. In this paper, we therefore attempt to reconstruct the battery of practices that implemented the political decision to (non)judge some of the leaders of the last Argentine dictatorship in “The Cause of the Judges” and the context, or that provincial political-politico-judicial plot into which this case is inserted and which acts as a limitation on the possibility of counter-justice: of being able to exercise a judicial type of act with respect to a defendant who generally escapes justice (Foucault, 1979: 73).